2014
DOI: 10.1128/cvi.00430-13
|View full text |Cite
|
Sign up to set email alerts
|

Safety, Immunogenicity, and Antibody Persistence following an Investigational Streptococcus pneumoniae and Haemophilus influenzae Triple-Protein Vaccine in a Phase 1 Randomized Controlled Study in Healthy Adults

Abstract: cWe investigated a protein-based nontypeable Haemophilus influenzae (NTHi) and pneumococcal (HiP) vaccine containing pneumococcal histidine triad D (PhtD), detoxified pneumolysin (dPly), and NTHi protein D (PD) in adults. In a phase I study, 40 healthy 18-to 40-year-old subjects were randomized (2:2:1) to receive two HiP doses administered 60 days apart, with or without AS03 adjuvant (HiP-AS and HiP groups, respectively), or Engerix B (GlaxoSmithKline, Belgium) as a control. Safety, antibodies, and antigen-spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 42 publications
1
20
0
1
Order By: Relevance
“…Previous studies of adults Ն65 years of age and younger adults administered PhtD vaccines reported a tendency toward higher reactogenicity with AS02 V -than with alum-containing formulations (27). An increase in reactogenicity was also observed in a study of a vaccine containing PhtD, dPly, and protein D administered with the AS03 adjuvant system compared to with antigen alone (28).…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…Previous studies of adults Ն65 years of age and younger adults administered PhtD vaccines reported a tendency toward higher reactogenicity with AS02 V -than with alum-containing formulations (27). An increase in reactogenicity was also observed in a study of a vaccine containing PhtD, dPly, and protein D administered with the AS03 adjuvant system compared to with antigen alone (28).…”
Section: Discussionsupporting
confidence: 48%
“…In studies of elderly adults and adults -18 to 45 years of age, improved immune responses were seen with a PhtD vaccine containing the AS02 V adjuvant system compared to those with an alum adjuvant, and the reduced immune response to vaccines among elderly adults was partially restored to the level of vaccine-induced response observed in younger adults (27). The inclusion of the adjuvant system AS03 also enhanced immune responses to an investigational PhtD-dPly vaccine containing nontypeable Haemophilus influenzae protein D in adults -18 to 40 years of age (28).…”
mentioning
confidence: 76%
“…161 The second vaccine, developed in association with GlaxoSmithKline (GSK) Biologicals is a trivalent vaccine consisting of recombinant, formaldehyde-detoxified Ply in combination with full-length PhtD lacking the signal peptide, and recombinant, non-typeable Haemophilus influenzae (NTH1) protein D (PD) expressed by both encapsulated and nonencapsulated variants. 162 In a recently reported phase I study, the vaccine was administered to healthy adults as 2 doses 60 days apart and found to be safe. Following immunisation, serum levels of antibodies against vaccine antigens increased markedly and remained elevated at day 420, while cellmediated immune responses (Th1 and Th17) were transiently activated.…”
Section: Pspa-based Vaccinesmentioning
confidence: 99%
“…Following immunisation, serum levels of antibodies against vaccine antigens increased markedly and remained elevated at day 420, while cellmediated immune responses (Th1 and Th17) were transiently activated. 162 Immunogenicity was enhanced by inclusion of the adjuvant, AS03 (vitamin E + squalene in an oil-in-water emulsion).…”
Section: Pspa-based Vaccinesmentioning
confidence: 99%
“…The use of protein antigens may potentially provide serotype-independent protection and broader coverage of different strains of these bacteria (5-7). Recent trials have already shown promising results with protein antigens in the immunization of human subjects (8,9) and in experimental animal models (10,11) using the pneumococcal proteins Ply, CbpA, PspA, PcpA, and PhtD. Thus, the knowledge about the maturation of immune responses against protein antigens from respiratory pathogens might improve this new approach to vaccine development.…”
mentioning
confidence: 99%